Mineralocorticoid Receptor Antagonists - Ilaria Spoletini (International Cardiovascular Forum Journal, 2019)
The role and adverse effects of mineralocorticoid receptor overactivation in the pathophysiology of heart failure (HF) is wellrecognised. MR antagonists (MRAs) have been tested in HF and shown to be effective in improving outcomes. Steroid-type MRAs spironolactone and eplerenone, have been proven to reduce mortality in HFrEF. In patients with HFpEF, the TOPCAT trial found no significant benefits of spironolactone on cardiovascular outcomes. In order to overcome the limitations of existing steroidal MRAs, novel MRAs have been recently developed, finerenone and PF-03882845. These newer agents aim to optimise the benefits of MRAs and reduce their side-effects, especially hyperkalaemia.